2023
DOI: 10.3390/antibiotics12030474
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Properties of Eucalyptus globulus Essential Oil against MRSA: A Systematic Review

Abstract: Antimicrobial resistance is a huge threat against the public health sphere and is a major cause of global mortality and morbidity. Antibiotic misuse and overuse have led to the development of many resistant bacterial strains. One particular bacterium of concern is methicillin-resistant Staphylococcus aureus (MRSA), which is the most common resistant bacteria in humans. Antibiotic development has been unable to keep up with the rapid evolution of antibiotic-resistant organisms, and there is an urgent need to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 39 publications
0
11
0
1
Order By: Relevance
“…In this context, anti-bacterial activity of 1,8-Cineol was demonstrated against various strains of E. coli (including Avian Pathogenic E. coli ; APEC) isolated from broiler chicken [ 43 ]. However, further investigations concerning the anti-microbial activity revealed that the fruit oil of E. globulus was hardly active against multidrug-resistant (MDR) Gram-negative bacteria [ 44 , 45 ]. Acknowledged limitations of the clinical application of 1,8-Cineol are its instability, the short half-life and its vitality.…”
Section: Anti-microbial and Anti-viral Potentialmentioning
confidence: 99%
“…In this context, anti-bacterial activity of 1,8-Cineol was demonstrated against various strains of E. coli (including Avian Pathogenic E. coli ; APEC) isolated from broiler chicken [ 43 ]. However, further investigations concerning the anti-microbial activity revealed that the fruit oil of E. globulus was hardly active against multidrug-resistant (MDR) Gram-negative bacteria [ 44 , 45 ]. Acknowledged limitations of the clinical application of 1,8-Cineol are its instability, the short half-life and its vitality.…”
Section: Anti-microbial and Anti-viral Potentialmentioning
confidence: 99%
“…The sub-lethal dose was considered to be between 10 and 25 μg/mL, which resulted in survival rates of 52.2 and 36.2% in HepG2 cells. It was observed that Eucalyptol insignificantly inhibited cell growth up to a concentration of 25 μg/ml ( 54 ).…”
Section: Resultsmentioning
confidence: 99%
“…It still has to be acknowledged that the lack of statistical significance for motility at 120 h upon treatment with 1 mg/mL, potentially due to the statistical approach used and the sample size, does not imply a lack of biological relevance since, indeed, motility is almost completely suppressed. Nonetheless, literature shows a good amount of work that proves antibacterial activity of this EO, both alone and in combination with other agents, even against strains of methicillin-resistant Staphylococcus aureus (MRSA) bacteria, with MIC values ranging from 0.032 to 10 mg/mL 35 .…”
Section: Discussionmentioning
confidence: 99%